In vitro Release Kinetics Study of Ranolazine from Swellable Hydrophilic Matrix Tablets - Uddin, Mohammad Nezab; Ahmed, Ishtiaq; Roni, Monzurul Amin; Islam, Muhammad Rashedul; Rahman, Mohammad Habibur; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2010)
The objective of this study was to design oral sustained release matrix tablets of Ranolazine using hydroxypropyl methylcellulose (HPMC) as the retardant polymer and to study the effect of formulation factors such as polymer proportion and polymer viscosity on the release of drug. In vitro release studies were performed using USP type II apparatus (paddle method) in 900 mL of 0.1N HCl at 100 rpm for 12 hours. The release kinetics was analyzed using the zero-order, first order, Higuchi and Korsmeyer-Peppas equations to explore and explain the mechanism of drug release from the matrix tablets. In vitro release studies revealed that the release rate decreased with increase in polymer proportion and viscosity grade. Mathematical analysis of the release kinetics indicated that the nature of drug release from the matrix tablets was dependent on drug diffusion and polymer relaxation and therefore followed non-Fickian or anomalous release. The developed controlled release matrix tablets of Ranolazine prepared with high viscosity HPMC extended release up to 12 hours. Key words: Ranolazine; Sustained release; Methocel E50 Premium LV; Methocel K100LV CR; Methocel K4M CR; Methocel K15M CR. DOI: 10.3329/dujps.v8i1.5333 Dhaka Univ. J. Pharm. Sci. 8(1): 31-38, 2009 (June)